Perancangan Perbaikan Proses Bisnis menggunakan Metode Business Process Improvement (BPI) (Studi Kasus: CV. Indomedia Pustaka) - Wildan Arrizal Wahyu Sutomo; Intan Sartika Eris Maghfiroh; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
CV Indomedia Pustaka was established as a company with a focus on book publishing. In running the business process CV. Indomedia Pustaka has problems with the inconsistency of the completion time for each book to be published. This will pose a risk to the CV publisher. Indomedia Pustaka. To be able to help solve problems, the first thing that needs to be done is to identify business processes in detail to be able to solve existing problems. There are four steps in the identification process: breakdown, modeling with Business Process Model and Notation, fine tuning, and validation (BPMN). Value Added Assessment (VAA) and fishbone diagrams were used to analyze the problem. Simplification is the third step of Business Process Improvement (BPI), and it is determined that six business processes need to be improved. As an additional step, the proposed business process is put through a bizagi modeler simulation comparison to see how much time can be saved by implementing it than the current one. On the recommendation of the manuscript checking business process, an increase of 42.95% was carried out. Recommendations for editing manuscripts also increased by 33.24%. The script layout business process has increased by 3.37%. The recommendation for book cover design decreased by 9.11%. However, the recommendation for author approval experienced a significant increase of 49.95% and the recommended production business process also increased by 8.76%.